Study of wind energy potential at selected wind speed stations in Peninsular Malaysia using weibull distribution function - Shoib, Abdul Rashid (2022)
Wind energy is considered one of the fastest-growing and most used renewable energy sources which can produce electricity without any harm to the environment. However, the application of wind energy is not thoroughly undertaken all over the world. In this study, wind characteristics and wind energy potentials in three different wind stations in Peninsular Malaysia located in Chuping, Kuantan, and Melaka have been analysed at different altitudes starting from the standard 10 m height up to 150 m height above sea level. Wind speed seasonable variations and prevailing wind directions are also thoroughly studied. The analysis technique was based on two-parameter Weibull distribution function over three recent consecutive years starting from 2018 up to 2020 to identify the potentiality of the wind as a source of energy generation in these respective sites. The results show that the monthly highest mean wind speeds were 4.42 m/s, 2.96 m/s, and 2.17 m/s in Melaka, Kuantan, and Chuping, respectively. The highest most probable wind speed was 4.70 m/s and the wind speed carrying maximum energy was 1.74 m/s, both occurred in Melaka in 2019. The yearly highest Weibull shape parameter was 1.69 and the scale parameter was 2.96 m/s. Among the three stations studied, Melaka has shown the highest wind power potentials with an average value of 26.10 W/m2, followed by Kuantan with 12.71 W/m2 and Chuping with 6.80 W/m2 wind power densities. The corresponding wind energy densities were 595.58 kWh/m2/year, 111.37 kWh/m2/year, and 228.65 kWh/m2/year for Chuping, Kuantan, and Melaka stations respectively. The prevailing wind directions are northeast at both Kuantan and Melaka stations, and west and southwest direction at Chuping station. It is therefore concluded that although the potential of the wind power of the sites covered in the present study is considerable, they are suitable for small-scale power generation applications only